2018
DOI: 10.1002/app.46894
|View full text |Cite
|
Sign up to set email alerts
|

Efficient adsorptive extraction materials by surface protein‐imprinted polymer over silica gel for selective recognition/separation of human serum albumin from urine

Abstract: In this study, we report the development of adsorptive extraction materials by surface protein‐imprinted polymers (MIPs) over silica gel for selective recognition/separation of human serum albumin (HSA) from urine. The HSA‐imprinted polymers prepared on silica particle had at interface between the silica gel and different MIPs greatly produced enrichment for the binding of protein from the urine. The solid‐phase extraction of the optimized polymer layer was prepared by copolymerization of methacrylic acid (MAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…These IF values achieved indicate that the inorganic salts in s.urine exhibited more positive synergetic effect towards the ATP binding of MIP, which has binding sites of triphosphates of ATP compared to the NIP; the previous studies observed that the ATP imprinted polymer towards phosphates salts (monosodium hydrogen phosphate) binding capacity is more, compared to the ATP that has triphosphates, and also the MIP has similar binding sites [30]. A similar observation also reported that the binding capacity of a cryogel towards template human serum albumin (HSA) present in non-diluted serum is 390.2 mg/g whereas the binding capacity in binding studies is 25.9 mg/g [55], and also in our previous work reported, MIP towards HSA showed maximum adsorption capacity in urine (129.5 mg/g) whereas the binding capacity in binding studies is 86.7 mg/g [40]. The UA [53,54], creatinine [54], and HSA [56] in the human urine are found to be as ∼0.63-13.6 mM, ∼2.12-17.1 mM, and ∼0.2-0.39 µM, respectively.…”
Section: Regeneration and Application To Human Urine Samples Of Adenosupporting
confidence: 79%
See 4 more Smart Citations
“…These IF values achieved indicate that the inorganic salts in s.urine exhibited more positive synergetic effect towards the ATP binding of MIP, which has binding sites of triphosphates of ATP compared to the NIP; the previous studies observed that the ATP imprinted polymer towards phosphates salts (monosodium hydrogen phosphate) binding capacity is more, compared to the ATP that has triphosphates, and also the MIP has similar binding sites [30]. A similar observation also reported that the binding capacity of a cryogel towards template human serum albumin (HSA) present in non-diluted serum is 390.2 mg/g whereas the binding capacity in binding studies is 25.9 mg/g [55], and also in our previous work reported, MIP towards HSA showed maximum adsorption capacity in urine (129.5 mg/g) whereas the binding capacity in binding studies is 86.7 mg/g [40]. The UA [53,54], creatinine [54], and HSA [56] in the human urine are found to be as ∼0.63-13.6 mM, ∼2.12-17.1 mM, and ∼0.2-0.39 µM, respectively.…”
Section: Regeneration and Application To Human Urine Samples Of Adenosupporting
confidence: 79%
“…The removal of ATP and formation of an imprinted polymer layer on PS with MBA crosslinker, and three functional monomers was confirmed by IR spectroscopy (Figure 2A). The IR bands of functional groups of ester and amide carbonyls were found at 1728 and 1657 cm −1 , respectively and the acid functional group at 1710 cm −1 was merged between amide and ester functional groups and a similar observation was also reported [40]. The -OH and -NH broad band which is absent in IR spectrum of PS at 3430 cm −1 and present in the IR spectrum of MIP and NIP whereas in the case of ATP, it was found as a broadband at 3356 cm −1 ; this is attributed to the presence of phosphoric acid -OH functional groups.…”
Section: Uv-vis and Ir Spectroscopy And Thermogravimetric Analysis Ofsupporting
confidence: 76%
See 3 more Smart Citations